1988
DOI: 10.1093/ageing/17.6.401
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age Upon the Affinity of Microsomal Mono-Oxygenase Enzymes for Substrate in Human Liver

Abstract: Although the clearance of many oxidized drugs falls with age, a corresponding fall in the maximal activities of drug metabolizing enzymes has not been noted. The possibility of a fall in enzyme affinity for substrate with age, which could account for the observed changes, has not previously been investigated in human liver. We have studied the kinetics of the microsomal mono-oxygenase 7-ethoxycoumarin-O-de-ethylase in 17 human liver biopsy specimens. No correlation was observed between age and microsomal prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…These findings are consistent with other studies (George et al, 1995;Stevens et al, 2003). As in previous reports (Wynne et al, 1988), K m values did not differ significantly among the four age groups (Table 1). These findings indicate that the reduced intrinsic clearance in groups A and D is attributable to decreased V max values (Table 2), whereas the qualitative nature of the enzyme (indicated by K m values) does not differ significantly with age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with other studies (George et al, 1995;Stevens et al, 2003). As in previous reports (Wynne et al, 1988), K m values did not differ significantly among the four age groups (Table 1). These findings indicate that the reduced intrinsic clearance in groups A and D is attributable to decreased V max values (Table 2), whereas the qualitative nature of the enzyme (indicated by K m values) does not differ significantly with age.…”
Section: Discussionsupporting
confidence: 93%
“…For drugs metabolized by first order kinetics, the affinity of the enzyme for substrate is an important determinant of reaction rate at low substrate concentrations. In a previous study (Wynne et al, 1988), no age-related changes were found in enzyme affinity. In our study, we evaluated effect of age on the metabolite formation rate and on the affinity, as well as on the estimated intrinsic clearance (V max /K m ).…”
Section: Discussionmentioning
confidence: 65%
“…Age-associated changes in body composition may also affect the V d or Q of a drug. [41] Although CYP activity in human liver microsomes, cultured hepatocytes and liver slices is not affected by the age of the donor, [39,42] CYP2C19 activity shows a decrease with age and has higher interindividual variability in older subjects. [15] In the present analysis, differences in the clearance of roflumilast were not associated with age, whereas clearance of roflumilast N-oxide was estimated to decrease by 25.6% between the ages of 40 and 75 years.…”
Section: Discussionmentioning
confidence: 99%
“…We have investigated total microsomal protein content, which is a general indicator of the content of membrane-bound enzymes, in livers from humans over a wide age range and have noted no decrease (Woodhouse et al 1984;Wynne et al 1988). We have investigated total microsomal protein content, which is a general indicator of the content of membrane-bound enzymes, in livers from humans over a wide age range and have noted no decrease (Woodhouse et al 1984;Wynne et al 1988).…”
Section: Human Studiesmentioning
confidence: 99%